Regulation of MYB Transcription Factors of Anthocyanin Synthesis in Lily Flowers - Yin, Xiaojuan; Zhang, Yibing; Zhang, Li; Wang, Baohua; Zhao, Yidi; Irfan, Muhammad; Chen, Lijing; Feng, Yulong (Frontiers in Plant Science, 2021)
Flower color is the decisive factor that affects the commercial value of ornamental flowers. Therefore, it is important to study the regulation of flower color formation in lily to discover the positive and negative factors that regulate this important trait. In this study, MYB transcription factors (TFs) were characterized to understand the regulatory mechanism of anthocyanin biosynthesis in lily. Two R2R3-MYB TFs, LvMYB5 and LvMYB1, were found to regulate anthocyanin biosynthesis in lily flowers. LvMYB5, which has an activation motif, belongs to the SG6 MYB protein subgroup of Arabidopsis thaliana. Transient expression of LvMYB5 indicated that LvMYB5 can promote coloration in Nicotiana benthamiana leaves, and that expression of LvMYB5 increases the expression levels of NbCHS, NbDFR, and NbANS. VIGS experiments in lily petals showed that the accumulation of anthocyanins was reduced when LvMYB5 was silenced. Luciferase assays showed that LvMYB5 can promote anthocyanin synthesis by activating the ANS gene promoter. Therefore, LvMYB5 plays an important role in flower coloration in lily. In addition, the transient expression experiment provided preliminary evidence that LvMYB1 (an R2R3-MYB TF) inhibits anthocyanin synthesis in lily flowers. The discovery of activating and inhibitory factors related to anthocyanin biosynthesis in lily provides a theoretical basis for improving flower color through genetic engineering. The results of our study provide a new direction for the further study of the mechanisms of flower color formation in lilies.